Multilayered refill friction stir spot welding of AA2024 and aluminum foils for electric vehicle battery application - Gera, Dennis Balbino (2020)
Different processes are currently being used to weld aluminum and copper in a multilayered configuration in battery pouches for the automotive industry. The methods most used are mechanical joint, ultrasonic welding, laser welding, and resistance spot welding. However, these techniques have limitations such as added mass, cracks, intermetallic compound formation, and thermal conductivity. Refill Friction Stir Spot Welding (refill FSSW) is an alternative process for welding overlap joints. In this work, the microstructure and properties of a multilayered weld of AA2024/CP-Al produced by refill FSSW were investigated. CP-Al foils and AA2024 sheets with thicknesses of 0.013 mm and 0.3 mm, respectively, were used. Statistical analysis was conducted to assess the influence of processing parameters on the joint's mechanical properties, process temperature, contact resistance, and microstructural features. Specimens with up to 50 layers of CP-Al foils were successfully welded. Response surface methodology indicated that plunge speed was significantly influential to LSS and process temperature; plunge speed was found to influence process temperature significantly, and rotational speed showed no influence in any of the investigated properties. The one-factor-at-a-time analysis showed that plunge depth, plunge speed, and rotational speed alter the AA2024 island's morphology, the bottom sheet's deformation, and the number of unbonded interfaces in the center of the weld. Microstructural analysis depicted intermetallic compounds, eutectic constituents, and unbonded foils; however, these features were not detrimental to the weld's mechanical properties. A maximum LSS of 1890 N, and minimum process temperature and contact resistance of 167ºC and 0.183 mΩ, respectively, were found. Therefore, mechanical properties were superior to aerospace application requisites, and contact resistance values are smaller than conventional lithium-ion batteries' internal resistance. Infrared analysis showed that temperatures below 80ºC are obtained at 30 mm from the welding tool, indicating the possibility of using refill FSSW in batteries while avoiding cell degradation.